Pelaksanaan Prosedur Pengujian Asersi LPPDK pada Audit Dana Kampanye Tahun 2024 Oleh KAP LMR (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the implementation of campaign finance audit procedures and evaluate their conformity with applicable quality standards. The case study was conducted at the Public Accounting Firm (KAP) Luthfi Muhammad & Partners. The data source was obtained from interviews with partners, the head of the audit implementation team, and members of the campaign fund auditors of KAP Luthfi Muhammad & Partners. The research results showed that KAP Luthfi Muhammad & Partners did not make direct visits to the clients concerned when collecting the required reports and supporting evidence because it was done via the SIKADEKA website. At the stage of auditing campaign funds, KAP Luthfi Muhammad & Partners has referred to KPU regulations and applicable audit standards. Namely PKPU No. 18 in 2023.